Computational analysis of dynamics in an agent-based model of cognitive load and reading performance - Ghanimi, Hayder M. A.; Ab. Aziz, Azizi (Springer, 2018)
To avoid the development of cognitive load during task-specific actions, technologies like companion robots or intelligent systems may benefit from being aware of the dynamics of related mental performance constructs. As a first step toward the development of such systems, this paper uses an agent-based approach to formalize and simulate cognitive load processes within reading activities, which may involve specific assigned task. The obtained agent-based model is analysed both by mathematical analysis and automated trace evaluation. Based on this description, the proposed agent-based model has exhibited realistic behaviours patterns that adhere to the psychological and cognitive literature. Moreover, it is shown how the agent-based model can be integrated into intelligent systems that monitor and predict cognitive load over time and propose intelligent support actions based on that.